Family Socialisation in Empowerment of Young Girls in Manipur - Mao, Chakho Kaya (JOURNAL OF INDIAN EDUCATION, 2015)
Women in Manipur are not empowered in true sense and thereby, this article attempts to probe the nature of the role of socialisation of young girls to find some avenues to empower them. It specifically focuses on the process of family socialisation in gender construction among the Christian families in Manipur. This study also examines how the process of family socialisation impacts the empowerment of young girls.